Audit Sistem Informasi Sistem Kunjungan Perpustakaan Menggunakan Framework COBIT 5 : Studi Kasus : SMK Negeri 1 Banyumas - M Afrian Maulana; Satria Dwi Nurwicaksana; Dominic Dinand Aristo; Dendi Putra Prakoso; Jeffri Prayitno Bangkit Saputra (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
One of the benefits of the development of information systems is to increase effectiveness, efficiency and convenience in various aspects of technological life, especially in the scope of education, such as at SMK Negeri 1 Banyumas which implements a library visit system. But there are also challenges in its implementation, such as theft of personal data and misuse of data by irresponsible people. By conducting an information system audit, we can better understand the weaknesses of the system, for example, using COBIT 5 to view and evaluate the information system. as in the questionnaire that we distributed shows that there are 79% of students feel safe about the library visit system and 4.8% of students feel that the library visit system is not secure enough for almost the same reasons such as the authentication system that only relies on a username in the form of NIS and no password. From this data we can provide recommendations such as implementing a password system and 2-factor authentication in order to better protect personal data, files, systems, networks, and so on so that the system becomes better and more secure.